2016
DOI: 10.1136/gutjnl-2015-310691
|View full text |Cite
|
Sign up to set email alerts
|

Increased uptake and improved outcomes of bowel cancer screening with a faecal immunochemical test: results from a pilot study within the national screening programme in England

Abstract: Markedly improved participation rates were achieved in a mature gFOBt-based national screening programme and disparities between men and women were reduced. High positivity rates, particularly in men and previous non-respondents, challenge the available colonoscopy resource, but improvements in neoplasia detection are still achievable within this limited resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
162
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(174 citation statements)
references
References 35 publications
10
162
1
1
Order By: Relevance
“…For instance, in a randomised controlled trial conducted in Spain, the PRs of colonoscopy group and faecal immunochemical test group were 34.2% and 24.6%, respectively (p<0.001) 17. A recent study from England reported that the PR using FOBT even increased to 66.4% in the National Health Service Bowel Cancer Screening Programme 16. Our analyses showed that previous FOBT was associated with increased uptake of subsequent colonoscopy.…”
Section: Discussionsupporting
confidence: 42%
“…For instance, in a randomised controlled trial conducted in Spain, the PRs of colonoscopy group and faecal immunochemical test group were 34.2% and 24.6%, respectively (p<0.001) 17. A recent study from England reported that the PR using FOBT even increased to 66.4% in the National Health Service Bowel Cancer Screening Programme 16. Our analyses showed that previous FOBT was associated with increased uptake of subsequent colonoscopy.…”
Section: Discussionsupporting
confidence: 42%
“…However, it has the disadvantages of a bowel preparation requirement and a risk for bowel rupture, and this method is not suitable for patients with anorectal stenosis, peritoneal irritation, severe cardiopulmonary function and other diseases . The faecal immunochemical test (FIT) is replacing the guaiac faecal occult blood test (gFOBT) in CRC screening . However, the diagnostic performance of the FIT depends on the cutoff value for a positive result .…”
Section: Introductionmentioning
confidence: 99%
“…2 The faecal immunochemical test (FIT) is replacing the guaiac faecal occult blood test (gFOBT) in CRC screening. [3][4][5] However, the diagnostic performance of the FIT depends on the cutoff value for a positive result. 6 Amitay et al 7 studied factors associated with falsepositive FIT results, including male sex, older age, obesity, smoking, aspirin use and newly detected nonneoplastic bowel disease.…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the results of the pilot study in England, which was performed to establish the acceptability and diagnostic performance of screening with the faecal immunochemical test (FIT) over the guaiac faecal occult blood test (gFOBT) 1. When comparing gFOBT to FIT, the uptake increased from 59.4% to 66.4%, positivity rate increased from 1.7% to 7.8% (at a cut-off level of 20 µg Hb/g faeces) and colorectal cancer (CRC) detection doubled.…”
mentioning
confidence: 99%